The First Muslim: A Psycho-Historical Study of the Life and Mission of Prophet Muḥammad - Nazir, Iymen (LECTURES: Journal of Islamic and Education Studies, 2025)
The tradition of Sīrah writing dates back to the time of the Prophet Muḥammad ﷺ and remains a subject of interest among Western writers. Western Sīrah writing is influenced by both the realistic as well as polemic approaches. Among the Western Sīrah writers, Lesley Hazleton holds a distinguished place for her contribution, The First Muslim: The Story of Muhammad. With a background in journalism, psychology and a good hold on Middle Eastern studies, Hazleton portrays the life of Prophet Muḥammad ﷺ in a narrative manner. The work is the psychological interpretation of the events of the life of Muḥammad ﷺ as portrayed by the author. Hazleton attempts to narrate a realistic image of the life and environment of Muḥammad ﷺ. The paper employs historical-analytic and textual analysis to critically examine Lesley Hazleton’s work on Prophet Muḥammad ﷺ. The paper analyses Hazleton’s work, focusing on her narrative approach, psychological interpretation, and use of literary methods. While Hazleton succeeds in portraying a figure often distorted in the West, her secular framing and psychological interpretations contradict Islamic understandings of prophethood, revelation, and divine mission.